Correlações de imagens por biospeckle de superfícies rugosas: simulações e experimentos - Pereira, Alexsandro de Farias (2012)
In this work, it was studied theoretically and experimentally biospeckle technique for analysis of rough surface with application to the investigation of biological activity. The theoretical study was conducted using light scattering theory, in particular a first order perturbation method, seeking to obtain the scattering cross-section per unit area of rough surface. Once given the cross-section, it was possible to obtain the distribution of intensities in a certain region of space as a function of time, allowing the comparison of different light distributions in different instants. The experimental investigation was made from the comparison of speckle patterns recorded (by a CCD camera) at different time instants produced from scattering of coherent light at 635 nm from a freshly harvested plant leaf. The parameter of comparison used was the Pearson correlation coefficient. The experimental result obtained from the correlation coefficient versus time showed a temporal evolution type exponential decay, indicating a degradation behavior of the leaf chemically active and regulated by equations rate. The theoretical result of the correlation function of time, obtained by simulation, also showed a behavior type exponential decay indicating a good agreement with experimental results.